COVID-19 and labour market inequality in South Africa - Köhler, Timothy (School of Economics, 2025)
In 2020, the world was gripped by the COVID-19 pandemic. Beyond its health implications, the pandemic led to unprecedented economic contractions and one of the largest increases in poverty and income inequality to date. Effects on labour markets are of particular interest given their dominant role in determining wellbeing. Existing evidence reveals substantial, regressive effects globally. This holds particular relevance in South Africa, measurably the most unequal country in the world, primarily due to the nature of its labour market, which also experienced one of the most stringent lockdowns globally. This thesis provides a micro-econometric examination of the aggregate and heterogenous labour market effects of the pandemic in South Africa. To do so, it employs descriptive and quasi-experimental econometric techniques applied on nationally representative, individual-level household survey data. After providing a synthesised review of the extensive international literature, the first substantive contribution concerns aggregate and between-group adjustments to employment and working hours. I estimate substantial aggregate job loss accompanied by a surge in inactivity, and document significant regressivity in both the short- and longer-terms, thus reinforcing pre-existing inequalities on both the extensive and intensive margins. I reveal the principal roles of two key features of the pandemic labour market - remote work ability and ‘essential' worker status - in explaining these outcomes. Modelling the evolution of outcome determinants suggests some persistent changes to the structure of the labour market. In my second substantive contribution, I analyse the evolving level and nature of wages and wage inequality. I first characterise the non-negligible, non-randomly distributed missing wage data. After obtaining reliable estimates through parametric techniques, I estimate extremely high and stable pre-pandemic inequality levels. At the pandemic's onset, I show that wages increased primarily due to an inequality-enhancing composition effect, driven by a regressive job loss distribution related to the two aforementioned features. Inequality-reducing within-worker wage gains are also evident, but the dominance of the composition effect resulted in a large but transient increase in inequality on net. Persistent changes to wage determinants drove wages and wage inequality back toward their pre-pandemic levels as the labour market recovered. The third contribution concerns the role of a key policy globally - sector-specific restrictions. I exploit temporal and between-industry variation induced by these to estimate their causal effect on employment. The analysis isolates how much job loss was attributable to this policy relative to other pandemic-related factors. I find significant negative effects, and estimate that they accounted for two-thirds of the total employment decline. This reflects both the severity of South Africa's restrictions but additionally that job loss would have still occurred in their absence, consistent with the literature. I further take advantage of overlap in policy variation and data collection periods to examine heterogeneity by policy stringency and sectoral formality, highlighting disproportionate effects on informal workers. The thesis concludes with a summary of key findings, limitations, and implications for future research.